Transformational Leadership Practices and Employee Engagement: Meaningfulness of Work and Personal Resources as Mediators - Putri Hardanti Gita Larasati; Veronika Agustini Srimulyani; F. Anif Farida (Politeknik Negeri Batam, 2023)
Changes in work life such as changes in working hours and changes in work patterns are the effect of the Covid-19 pandemic, which must be addressed positively by company leaders with employees so that they continue to work professionally. The purpose of empirical studies is to analyze the direct and indirect influence of transformational leadership (T.L.) on E.E. through meaningfulness of work (M.W.) and personal resources (P.R.). The respondents of the study were 134 employees at CV X Madiun City. The test was carried out by path analysis and Sobel test. The results of hypothesis testing show that: 1) T.L. significantly increases E.E., M.W., and P.R.; 2) M.W. increases P.R. significantly, and mediates the effect of T.L. on E.E. significantly; 3) P.R. significantly increase E.E. and mediate the effect of T.L on E.E significantly.